Elemental Sulfur-Based Autotrophic Denitrification in Stoichiometric S0/N Ratio: Calibration and Validation of a Kinetic Model - Levican-Jaque, G; Huilinir-Curio, C; Montalvo-Martinez, S; Yanez-Sevilla, D; Acosta-Cordero, L (Elsevier Ltd, 2020)
The inclusion of S0 hydrolysis in a kinetic model of autotrophic denitrification has been recently proposed; however the model has not been calibrated or validated yet. Thus, a new methodology was developed and applied to calibrate and validate this kinetic model for the first time. An inoculum adapted from a poultry wastewater treatment plant at stoichiometric S0/NO3− ratio was used. The model was calibrated with batch data (initial nitrate concentrations of 50 and 6.25 mg NO3−-N/L) at an S0/N ratio = 2.29 mg S/mg N and validated with seven different batch data. The sensitivity analysis showed that the most sensitive parameters are related to S0 hydrolysis. The kinetic model was successfully calibrated with the new methodology and validated, with Theil inequality coefficient values lower than 0.21. Thus, the proposed model and methodology were proved to be well suited for the simulation of elemental sulfur-based autotrophic denitrification in batch systems. © 2020 Elsevier Ltd